Alamo - Alamo (Motion picture : 2004); Hancock, John Lee; Johnson, Mark, 1945 December 27-; Howard, Ron, 1954-; Bohem, Leslie; Gaghan, Stephen; Semler, Dean, 1943-; Burwell, Carter; Beason, Eric L.; Corenblith, Michael; Orlandi, Daniel; Thornton, Billy Bob; et al. (Burbank, CA Touchstone Home Entertainment Distributed by Buena Vista Home Entertainment, 2004)
Retells the story of the historic 1836 battle in the Texan War of Independence. Facing 4,000 Mexican troops, 186 Texan soldiers and volunteers - including William Travis, Davy Crockett, and Jim Bowie - retreat within the walls of the Alamo, a Franciscan mission that was converted into a military fort. Once inside, the men prepare themselves for what will be a bloody battle to the death. U.S. General Sam Houston leads the charge from the outside. The Texans held the fort for 13 days under siege by General Santa Anna.
Title from @.
Special features: walking in the footprints of heroes: learn about David Crockett, William Travis, Jim Bowie and Sam Houston; deleted scenes with optional commentary by John Lee Hancock; return of a legend: the making of 'The Alamo' - a behind-the-scenes look; deep in the heart of Texans.
Director of photography, Dean Semler ; editor, Eric L. Beason ; music, Carter Burwell ; costume designer, Daniel Orlandi ; production designer, Michael Corenblith.
Billy Bob Thornton, Dennis Quaid, Jason Patric, Patrick Wilson, Jordi Molla, Emilio Echevarria, Marc Blucas, Leon Rippy.
MPAA rating: PG-13; for sustained intense battle sequences.
DVD; NTSC; region 1, widescreen presentation (aspect ratio 2.35:1) enhanced for 16x9 televisions; Dolby Digital, DTS, SDDS.
Keywords: Crockett, Davy -- 1786-1836 -- Drama; Bowie, Jim -- 1796?-1836 -- Drama; Houston, Sam -- 1793-1863 -- Drama; 1836; Alamo (San Antonio, Tex.) -- Sitio, 1936; Alamo (San Antonio, Tex.) -- Siege, 1836; Texas -- San Antonio; Historical films; War films; Western films; Feature films; Video recordings for the hearing impaired; Historical films; Drama